(untitled) (Ameghiniana, 2023)
Within the Order Notoungulata, considered the most diverse and abundant clade of South American native ungulates, Interatheriidae (late Paleocene-Late Miocene) is one of the best-known and most derived families. Most of the interatheriids described during late 19th century was erected from specimens collected from the proliferous Santa Cruz Formation (Santacrucian SALMA; Burdigalian-early Langhian), Santa Cruz Province (Argentina). One of the most important interatheriids is Protypotherium, due to its diversity and wide distribution in Bolivia, Chile, Uruguay, and, especially, Argentina, which was revised more than a century ago and from which most of the species were considered Typotheria incertae sedis. Despite this, several species were erected within this genus by diverse authors in the last years. This contribution provides the taxonomic revision of the pre- and post-Santacrucian species of Protypotherium that were not originally erected by Florentino Ameghino within the genus. We propose P. sinclairi and P. concepcionensis as junior synonyms of P. columnifer and P. colloncurensis, respectively, and conclude that Protypotherium includes P. antiquum, P. australe, P. praerutilum, P. compressidens, P. claudum, P. columnifer, P. minutum, P. distinctum, and P. colloncurensis. Finally, we present the most complete phylogenetic analysis of Interatheriidae, at both genus and species levels. It does not recover Protypotherium as a clade, due to the nesting of Caenophilus within the genus, and shows that this assemblage is the sister taxon of the clade constituted by Deseadan Progaleopithecus and Archaeophylus.